Choice of a suitable diabetes risk assessment tool in Nepal – can we learn from Canada? - Agarwal, Gina; Sathian, Brijesh; Agrawal, Sutapa (Nepal Journal of Epidemiology, 2016)
If the population can be made more aware about diabetes by the use of a risk assessment tool as an educational tool as well, it could help to curb the diabetes epidemic in Nepal. Education of the masses about diabetes risk factors, prevention, and complications is urgently needed, using clear and simple messages. National policy efforts can be strengthened and health outcomes improved when awareness is increased. Perhaps learning from Canada is a start, and Nepal will be able to make progress with something simple like ‘NEPAL-RISK’?